2016
DOI: 10.1007/s13201-016-0448-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical characterization of groundwater in around Tirupati Area, Chittoor District, Andhra Pradesh, South India

Abstract: In the management of water resources, quality of water is just as important as its quantity. The main aim of this study has been to assess the variability of groundwater parameters to develop water quality of Tirupati area and its suitability for domestic and irrigation purpose. Further, the samples were analyzed for pH, EC, TDS, carbonates, bicarbonates, alkalinity, chlorides, sulfates, hardness, fluoride, calcium, magnesium, sodium, and potassium. Based on the analytical results, chemical indices like percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The over dependence on groundwater for drinking, agricultural and industrial sector and different climatic and natural phenomenon causes coastal groundwater contamination (Srinivas et al 2015). Besides, different geochemical processes in groundwater governing the chemical characteristics of groundwater, is well documented in many parts of the world by many authors i.e., Montety et al (2008), Jalali (2009), Manjusree et al (2009), Thilagavathi et al (2012, Sivasubramanian et al (2013), Nagaraju et al (2014), Kumar et al (2015), Islam et al (2016a, b) and Balaji et al (2016). Geochemical studies of groundwater provide a better understanding of water quality and possible changes .…”
Section: Introductionmentioning
confidence: 99%
“…The over dependence on groundwater for drinking, agricultural and industrial sector and different climatic and natural phenomenon causes coastal groundwater contamination (Srinivas et al 2015). Besides, different geochemical processes in groundwater governing the chemical characteristics of groundwater, is well documented in many parts of the world by many authors i.e., Montety et al (2008), Jalali (2009), Manjusree et al (2009), Thilagavathi et al (2012, Sivasubramanian et al (2013), Nagaraju et al (2014), Kumar et al (2015), Islam et al (2016a, b) and Balaji et al (2016). Geochemical studies of groundwater provide a better understanding of water quality and possible changes .…”
Section: Introductionmentioning
confidence: 99%
“…It is indicated that electricity passes through media and articulated as microsiemens/cm or micromhos/cm (Nagaraju et al 2015;Balaji et al 2017). The EC values range from 400 to.…”
Section: Electrical Conductivity (Ec)mentioning
confidence: 99%
“…57L/8 falling in north latitudes 12 o 00'00'' and 12 o 15'00'' and longitude 78 o 15'00'' to 78 o 30'00'' covering an aerial extent of about 720 sq. km (Panneer et al, 2017), Parambikulam Aliyar, Coimbatore District, Tamil Nadu, India between the latitudes of 10 o 10' 00''N to 10 o 57' 20''N and the longitudes of 76 o 43' 20''E to 77 o 12' 30''E (Elangovan and Rani, 2017), Tirupati lies between 13 o 37' and 13 o 40' North latitude and 79 o 21' and 79 o 26' East longitude (Balaji et al, 2017), Alleppey district lies between latitude 9 o 35'00''N and longitude 76 o 10'00''E (Raj et al, 2017), The District of Dantewada covers an area of 9046.29 sq km. It comprises 608 villages, which are administratively divided into seven blocks of community development (Kumar et al, 2018) and Nalbari district, western part of the Assam and is situated between 26°8′30″N and 26°52′15″N latitude and 91°14′30″E and 91°38′10″E longitude (Swinscow, 1997) as shown in Fig.…”
Section: Selected Sitesmentioning
confidence: 99%